Analisis Yuridis Terhadap Pertimbangan Hakim Dan Putusan Hakim Perkara No 75/Pid.B/2021/Pn.Mad Dalam Tindak Pidana Pencurian ( Studi Kasus Di Pengadilan Negeri Madiun ) - Angga Pramodya Pradhana; Meirza Aulia Chairani; Retno Iswati; Denny Praptanto (Universitas Merdeka Madiun, 2022)
Abstrac–Humans are individual beings and social beings. As individual beings, humans have physical and spiritual elements, physical and psychological elements, and soul and body. The purpose of this study aims to determine the application of criminal sanctions to the crime of theft in criminal cases No: 75/Pid.B/2021/PN.Mad. This research was carried out at the Madiun District Court by making copies of decisions related to solving the problem of the crime of theft. Besides that, the researcher also conducts a literature study by examining books, literature and laws and regulations relating to the problems that will be discussed in the author's thesis. The findings obtained from this study are first, the application of criminal sanctions against the crime of theft in Criminal Case No: 75/Pid.B/2021/PN.Mad, namely violating Article 363 paragraph 1 (one) 3rd and 4th of the Criminal Code. In addition, the application of criminal sanctions imposed in the crime of theft committed by the defendant does not see the value at stake and the reasons for committing the crime, but whether or not the defendant committed the crime of theft. Second, the judge's consideration in imposing the sanction for the crime of theft in Criminal Case No: 75/Pid.B/2021/PN.Mad is based on evidence, namely witness testimony and the defendant's statement accompanied by evidence submitted by the Public Prosecutor and the facts presented by the Public Prosecutor. revealed in court. In addition, the criminal sanctions given are not aimed at destroying the future of someone who has committed a crime of theft, but to provide a deterrent effect, so as not to repeat the act and make that person better and beneficial to the country and nation.